Effect of smoking cessation on the likelihood of pancreatitis and pancreatic cancer - Xiao Han; Zouhua Xu; Dongmei Ma; Zhi Ling; Xiaowu Dong; Xuebing Yan; Yong Chen; Guotao Lu; Xudong Yin; Hongwei Xu (Tobacco Induced Diseases, 2024)
Introduction Tobacco smoking is a major risk factor for various diseases worldwide, including pancreatic exocrine diseases such as pancreatitis and pancreatic cancer (PC). Currently, few studies have examined the impact of smoking cessation on the likelihood of common pancreatic exocrine diseases. This study sought to determine whether smoking cessation would reduce pancreatitis and PC morbidity.